POLA PERESEPAN OBAT DISPEPSIA DI PUSKESMAS GADANG HANYAR PERIODE JANUARI – MARET 2023 - Asyfa Putri Ramadhani; sri rahayu; Ade Syarif Hakim (Jurnal Komunitas Farmasi Nasional, 2023)
According to Badan Pusat Statistik 2019 for the City of Banjarmasin, dyspepsia ranks 6th with a total of 25,085 cases. At the Puskesmas Gadang Hanyar, dyspepsia is the ten most common disease in 2022, ranking 4th with a total of 790 cases. So that the use of dyspepsia drugs will increase. Therefore it is necessary to look at the pattern of prescribing dyspepsia drugs at the puskesmas to ensure the availability of existing drugs so that they can support safety and ensure their effectiveness. The purpose of this study was to determine the pattern of prescribing dyspepsia drugs at the Puskesmas Gadang Hanyar for the period January - March 2023. This research was a descriptive study with retrospective data collection using a purposive sampling technique, obtained a sample of 403 prescriptions. The results showed that the most widely used drug class was the Proton Pump Inhibitor (PPI) class of drugs with a percentage of 203 (46.03%), the most widely used type of drug was omeprazole with 164 percentages (37.19%), treatment of dyspepsia The single highest percentage was omeprazole with 140 percentages (38.36%). and the most widely used combination of drugs, namely antacids and omeprazole with a percentage of 13 (34.21%).